Blockchain Technology In Healthcare: Potential Benefits And Barriers In Health Informatics (The Review of Diabetic Studies, 2024)
This study explores the application of blockchain technology within the healthcare sector, emphasizing its potential benefits and barriers in health informatics. By leveraging secondary data from a diverse range of academic publications, industry reports, and case studies, the research provides a comprehensive overview of how blockchain can be a transformative force in healthcare. The findings suggest that blockchain technology offers significant advantages, including enhanced data security, improved interoperability, and increased transparency. These benefits could lead to more efficient healthcare delivery, reduced costs, and better patient outcomes. However, the study also identifies several barriers to widespread blockchain adoption, such as technical complexity, regulatory challenges, scalability issues, and the need for standardized protocols. By addressing these obstacles, stakeholders can unlock the full potential of blockchain technology, ensuring a more secure and efficient future for health informatics. This study serves as a foundational resource for healthcare professionals, policymakers, and technologists aiming to navigate and implement blockchain solutions in the healthcare industry.